BIBLIOMETRIC ANALYSIS FOR USE OF TIME SERIES IN ANIMAL SCIENCE - Yavuz, Esra (My University, 2023)
In this study, bibliometric analysis was applied to time series, which has been widely used in animal science studies in recent years. In the method part of the study, a bibliometric analysis was carried out for time series commonly used in animal science studies. In the study is to determine the trends in recent years in the field of animal science, by examining 3895 studies with the term \"time series\" in the title of the article published within the scope of SCI-Expanded between 1980 and 2023, within the scope of bibliometric analysis. Statistical evaluations were calculated using the R software belonging to the \"bibliometrix\" package. All data were generated bibliographically from the WoS system in plain text format. Time series has been one of the most popular research areas due to its application in many different fields such as cell biology, plant sciences, zoology, animal science, etc. There are many authors' works in the field of time series. According to the analysis, a total of 3202 studies, such as articles, journals, books, etc. by 14154 authors, were published on time series in animal science. As a result of the analysis, in the 14154 authors, only 247 studies has been single authored documents of afromentioned topic. Time series in animal science examined within the scope of author’s collaboration that there were 0.275 authors per document. This study aims to conduct bibliometric analysis to determine the importance of time series in the field of agriculture, the number of publications by year, annual publication increase, and distribution by country and number of articles by keywords. The analysis results will be an important contribution to both readers and researchers.
Keywords: Bibliometric; Time series; Animal sciences